THE EFFECT OF CHICKEN MANURE TO GROWTH AND THE YIELD OF HIGH POTENCIAL RICES USING SRI METHOD - Nurjani, Putri Hermawati Mulyadi Safwan (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT The research aims to know the effect of manure and variety to both growth and rice"™s crop uses SRI method includes the interaction to tidal lands. The research carried out at Kalimas village, Sungai Kakap Sub District, Kubu Raya Regency. It was started in May to August 2018 by using Split Plot Design consistog P0 (0 ton/Ha), P1 (5 ton/Ha) and P2 (10 ton/Ha) while temporary Main Plot, the sub plot consist of V1 (Inpari 32 variety) and V2 (Situbagendit variety). Each treatment is repeated four times and 5 samples for each paddy farming. Variables which be observed are height, number of tilers, productive tillers, panicle length, grains weight per clusters, number of grains per panicle, percentage of filled grains, and 1000 grain weight. The result shows that manure affects on the entire variables, whereas variety significantly affects the height, length, and weight. However, the grains per panicle, the number of tillers and the percentage are not affected. According to this study, manure with proper dose is 10 tons/Ha will increase production, While the Situbagendit and Inpari 32 varieties showed significant differences compared to the SRI method.Keywords: Inpari 32 Variety, Manure, Situbagendit Variety, Sri Method.